Wireless ad hoc network using handheld devices / Siti Asmah Mahat - Mahat, Siti Asmah (2006)
This report describes the development and implementation of a wireless ad hoc network for mobile handheld devices. As users are increasingly mobile it is more and more common for users to meet and communicate without prior planning and in environments where there is little or no networking infrastructure. Such a network is known as an ad hoc network, where the network is of a dynamic nature without centralized administration. Current technology such as IEEE 802.1 lb wireless LAN can form ad hoc networks but is limited in that only single hop networks can be formed. This means that each node can only act as a host, whereas in a multi-hop ad hoc network all nodes act as routers. This project concentrated on the setting up a wireless ad hoc network testbed consists of one Personal Digital Assistant (PDA) and one wireless notebook. The implementation enabled the notebook and the Personal Digital Assistant (PDA) to form a multi-hop ad hoc network with 802.1 lb wireless cards.